MicroRNA regulation of vascular function. (19th July 2019) - Mellis, David; Caporali, Andrea
Abstract : MicroRNAs (miRNAs) are small non-coding RNAs that orchestrate genetic networks by modulating gene expression. Given their importance in vascular development, homeostasis and diseases, along with the technical feasibility in deploying their function in vivo, the so-called 'vascular miRNAs' have become key targets for therapeutic intervention. Herein, we have summarised the state-of-the-art on vascular miRNAs and we have discussed the role miRNA biogenesis and the extracellular vesicles (EVs) miRNA transport in vascular biology.